POPULASI, SEBARAN DAN ASOSIASI KEPUH (Sterculia foetida L.) DI KABUPATEN SUMBAWA NUSA TENGGARA BARAT - Arya Arismaya Metananda; Ervizal A.M. Zuhud; Agus Hikmat (Media Konservasi, 2015)
Kepuh (Sterculia foetida L.) is a multi-function plant that presently in danger of extinction. Various acts of illegal logging, convertion of the region, as well as their skin dormancy is a challenge in conservation kepuh in nature. As racing with these conditions, conservation efforts must be known in advance regarding kepuh’s  population, how the spatial distribution and association as well. This data is important as a basis of the policy making and action in the field of handling. Therefore, the research was conducted to identify the population of kepuh, spatial distribution of kepuh and associated with other spesies. This research was conducted in 12 districts in Sumbawa Regency through surveys and literature review. The result of exploration and single quadrat method were found 169 individuals (65 seedlings, 5 saplings, 14 poles, 85 trees) kepuh in 12 districts. Based on its distribution, kepuh was unevened these days. The patterns of kepuh’s distribution was clumped. This means  that socio ecologically the existence of food and beverage is concentrated in certain locations. On the other side of the socio biological clumped distribution also indicate social interaction/association among kepuh and other plants. Associations pattern shown, kepuh in nature are relatively positive. However, when it is viewed from the level of the association by applying Jaccard index showed that the associations were formed relatively weak (average value 0,38). Population presented infomation, distribution and distribution patterns and associations of kepuh would be the basis for sustainable management of kepuh in nature. Keyword: association, conservation, distribution, kepuh, population.